IMPROVING STUDENTS’ PRONUNCIATION SKILL USING ELSA SPEAK APPLICATION - Anggraini (Journey: Journal of English Language and Pedagogy, 2022)
The purpose of this research is to Introduce the ELSA Speak Application as media to improve students' pronunciation skills. English Language Speech Assistant is an acronym for ELSA. English Language Speech Assistant can be downloaded for free from AppStore or Google Play. complete with various features to improve the pronunciation and speaking of students with American accents by training them with various exercises to pronounce words/phrases/sentences correctly. Corresponding to the microphone icon that the learner can use directly to speak as the audio has been listened to.This research is an Action Research that aims to Improve students’ pronunciation skills using ELSA Speak Application. This research discusses how ELSA Speak Application as learning media can improve students’ pronunciation skills. The data were collected through a test of pronunciation and Interviews in Classroom action research. The researcher made three cycles and gave a score for each cycle. In the first cycle, the students’ Average score is 70 points, the second cycle is 75 points and the last cycle is 80 points. ELSA Speak application helps students pronounce a variety of words more easily and comprehensively. The results showed that the use of the ELSA Speak Application has provided convenience and benefits for students in improving their English Pronunciation skills by using the ELSA Speak application.